Hubungan Interaksi Edukatif Guru terhadap Minat Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam di Sekolah Dasar Islam Terpadu (SDIT) Mutiara Rahmah Balikpapan - Aghnina, Dian; Yusuf, Iskandar (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Interaction or communication is one of the challenges that often arise in the learning and teaching process in the world of education. Especially between teachers and students. When the teaching and learning process becomes less smooth, such as students are afraid and reluctant to actively participate in learning so that students do not understand the subject matter that has been explained, it is a negative impact of teachers who do not communicate well and clearly to their students, which will also affect students' interest in learning, especially in Islamic religious education subjects. The purpose of this study was to determine the relationship between teacher educational interaction and students on students' interest in learning in Islamic Religious Education subjects at SDIT Mutiara Rahmah Balikpapan. This study uses a quantitative approach with a correlation research type, namely to find the relationship between variable X, namely teacher educational interaction and variable Y, namely student interest in learning. Data collection methods used in this study were: observation, interviews, questionnaires with a population and sample of 50 respondents using saturated sampling. The findings of this study are supported by hypothesis testing, which is assisted by the use of IBM SPSS Statistics Version 25 software and the Pearson product moment correlation formula. The Sig. value was obtained. (2-tailed) of 0.000 and the level of significance of the study is known to be 5% or 0.05. Based on the predetermined standards, the results obtained are that the Sig. Value (2-tailed) < Significance Level, namely 0.000 < 0.05. The calculated r value> r table is 0.754> 0.279. The Pearson Correlations value between each connected variable has two asterisks, namely 0.754 **. So it can be concluded that there is a significant relationship between the educative interaction of teachers and students on students' learning interest in Islamic Religious Education subjects at SDIT Mutiara Rahmah Balikpapan.